Subcutaneous sarcoidosis: a clinical analysis of nine patients. Issue 9 (September 2016) - Ando, Masaru; Miyazaki, Eishi; Hatano, Yutaka; Nishio, Suehiro; Torigoe, Chihiro; Yamasue, Mari; Mukai, Yutaka; Nureki, Shin-ichi; Kadota, Jun-ichi
Abstract Subcutaneous sarcoidosis is the specific subset of cutaneous sarcoidosis frequently associated with systemic disease. However, the disease activity, severity, and prognosis have not yet been elucidated due to the limited number of reported cases. The purpose of this study was to identify the clinical, laboratory, and prognostic differences between subcutaneous sarcoidosis and other type of cutaneous sarcoidosis. All patients with sarcoidosis diagnosed histopathologically from 2000 to 2012 at our institution were enrolled. The clinical, laboratory, chest X-ray, and pulmonary function test results were retrospectively evaluated in the patients with cutaneous sarcoidosis. In the 130 patients with sarcoidosis, cutaneous sarcoidosis was diagnosed in 37 patients (28.4 %), and 9 (6.9 %) of these patients had subcutaneous sarcoidosis. The serum levels of soluble interleukin-2 receptor (sIL-2R) were significantly elevated in the group of patients with subcutaneous sarcoidosis in comparison to the patients with other types of cutaneous sarcoidosis, whereas there was no significant difference in the severity score between the two groups. Following a 2-year observation period, three patients were in remission, five patients demonstrated stable disease, and one patient had progressive disease. Subcutaneous sarcoidosis may be associated with the disease activity, although it was not found to be associated with the disease severity and it was not a predictive factor for the prognosis. Furthermore, the prevalence of subcutaneous sarcoidosis may be higher than that in previously reported series.